Impact of vehicles reliability on the purchasing costs of spare parts - Yu. D. Ishkin; N. S. Zakharov; E. G. Ishkina (Архитектура, строительство, транспорт)
The operation of road transport is associated with maintaining the serviceability of vehicles. Companies that operate vehicles have different approaches to ensuring their serviceability. Small ones, as a rule, carry out maintenance and repair of vehicles at service stations, while large and medium-sized companies provide conditions for carrying out technical service at their own base. In this case, they are faced with the need to stock with spare parts. It was found that the costs of spare parts account for up to 45 % of all operating costs, their reduction is possible with the correct approach to planning and organization of spare parts supply. This confirms the relevance of the research. As the main factor affecting the cost of spare parts purchasing, the authors proposed to consider the reliability of car units and assemblies. A regularity was established: the reliability of a vehicle decreases with the increase of its service life, while the need for spare parts and, consequently, the purchasing cost of spare parts increases. Spare parts stocks are planned in two groups – for maintenance and repairs. It is possible to plan the consumption of spare parts for maintenance based on the vehicle fleet and on the recommendations of the manufacturer, which regulates the frequency of replacement and the list of spare parts. It is advisable to plan the nomenclature of spare parts for current repairs based on vehicles reliability. Forecasting of spare parts stock based on reliability will allow to manage spare parts stock effectively, to minimize their shelf life and to avoid the purchase of unclaimed spare parts.